2020
DOI: 10.1371/journal.pone.0242725
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the mechanism of recognition of the 3’ splice site of the adenovirus major late promoter intron by the alternative splicing factor PUF60

Abstract: Pre-mRNA splicing is critical for achieving required amounts of a transcript at a given time and for regulating production of encoded protein. A given pre-mRNA may be spliced in many ways, or not at all, giving rise to multiple gene products. Numerous splicing factors are recruited to pre-mRNA splice sites to ensure proper splicing. One such factor, the 60 kDa poly(U)-binding splicing factor (PUF60), is recruited to sites that are not always spliced, but rather function as alternative splice sites. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
(82 reference statements)
3
8
1
Order By: Relevance
“…We have provided a high-resolution model of the FIR RRM1-2-FUSE interaction and presented a comprehensive structural analysis of RRM-ssDNA/RNA interactions. We observed distinct binding modes of different RRM-ssDNA interactions and no binding-induced RRM1-2 protein-protein interaction as postulated previously [11,21]. Together with ITC binding data, our structural data demonstrated that FIR RRM1 has the potential to interact with diverse ssDNA sequences, consistent with previous data that reported on the low specificity of this protein [11].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have provided a high-resolution model of the FIR RRM1-2-FUSE interaction and presented a comprehensive structural analysis of RRM-ssDNA/RNA interactions. We observed distinct binding modes of different RRM-ssDNA interactions and no binding-induced RRM1-2 protein-protein interaction as postulated previously [11,21]. Together with ITC binding data, our structural data demonstrated that FIR RRM1 has the potential to interact with diverse ssDNA sequences, consistent with previous data that reported on the low specificity of this protein [11].…”
Section: Discussionsupporting
confidence: 90%
“…Together with ITC binding data, our structural data demonstrated that FIR RRM1 has the potential to interact with diverse ssDNA sequences, consistent with previous data that reported on the low specificity of this protein [11]. Along with the previous structural studies [11,21], our crystal structures, which present different binding modes of the two bound dinucleotides, extend the repertoire of structural models for nucleotide interactions in FIR. The structural plasticity observed highlights the versatility of FIR RRMs in accommodating diverse oligonucleotide sequences, in agreement with published binding studies [11,21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…4a,b ). This residue mediates interdomain RRM1–RRM2 contacts in the PUF60 crystal structure 16 and may affect salt bridge formation. Rbm-39 encodes an RNA-binding protein, the human ortholog of which, RBM39, functions as a splicing factor and is involved in early spliceosome assembly 17 .…”
Section: Resultsmentioning
confidence: 99%
“…4a, b). This residue mediates interdomain RRM1-RRM2 contacts in the PUF60 crystal structure 14 , and may affect salt bridge formation. RBM-39 encodes an RNA binding protein, whose human ortholog, RBM39, functions as a splicing factor and is involved in early spliceosome assembly 15 .…”
Section: Mainmentioning
confidence: 99%